2022
DOI: 10.2196/34144
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Health Care Services Caused by the Adoption of Digital Health Technologies: Scoping Review

Abstract: Background Digital health technologies (ie, the integration of digital technology and health information) aim to increase the efficiency of health care delivery; they are rapidly adapting to health care contexts to provide improved medical services for citizens. However, contrary to expectations, their rapid adoption appears to have led to health inequities, with differences in health conditions or inequality in the distribution of health care resources among different populations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(96 citation statements)
references
References 73 publications
(185 reference statements)
5
90
0
1
Order By: Relevance
“…A lack of concrete solutions to address these barriers was mentioned [48]. It is likely that digital health cannot serve all populations equally well [71], which aligns with the results of a scoping review that investigated the inequities caused by the adoption of digital health technologies [92]. Some researchers indicated that older adults can also experience benefits by using digital health [53], whereas others suggested that telehealth is, at best, a partial solution for younger and fitter subpopulations [47,71].…”
Section: Influencing Factors Are More Complex Than Facilitators and B...mentioning
confidence: 90%
“…A lack of concrete solutions to address these barriers was mentioned [48]. It is likely that digital health cannot serve all populations equally well [71], which aligns with the results of a scoping review that investigated the inequities caused by the adoption of digital health technologies [92]. Some researchers indicated that older adults can also experience benefits by using digital health [53], whereas others suggested that telehealth is, at best, a partial solution for younger and fitter subpopulations [47,71].…”
Section: Influencing Factors Are More Complex Than Facilitators and B...mentioning
confidence: 90%
“…Because patients with CVD often have multiple comorbidities, there is an inherent risk of being confronted with different unrelated DHIs for individual comorbidities (e.g., hyperlipidaemia, hypertension). Patients with a lower education level are at a higher risk of not being able to engage with digital health technologies, especially at an older age [ 126 ].…”
Section: Roadblocks and Solutions To Implement Digital Health Interve...mentioning
confidence: 99%
“…For example, increasing digitization of health services can limit the access to and the availability of such services to those who have stable and reliable internet access. 20 Difficulties in accessing the internet can reduce access to essential social determinants of health: In a qualitative study, Baum and colleagues 21 highlight that limited internet access also limits access to (in particular higher) education, the housing market, employment options and social networks. This in turn can create a vicious cycle of social disadvantage and increasing health inequities.…”
Section: Living and Working Conditionsmentioning
confidence: 99%